Post-millennial gothic comedy, romance and the rise of happy gothic - Spooner, Catherine 1974- (London Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
Surveying the widespread appropriations of the Gothic in contemporary literature and culture, 'Post-Millennial Gothic' shows contemporary Gothic is often romantic, funny and celebratory. Reading a wide range of popular texts, from Stephenie Meyer's 'Twilight' series through Tim Burton's Gothic film adaptations of 'Sweeney Todd', 'Alice in Wonderland' and 'Dark Shadows', to the appearance of Gothic in fashion, advertising and television, Catherine Spooner argues that conventional academic and media accounts of Gothic culture have overlooked this celebratory strain of 'Happy Gothic'.
1. Consuming the Edible Graveyard: Gothic Lifestyles and Lifestyle Gothic -- 2. The images, for me, are the story': Tim Burton's Gothic Aesthetics -- 3. Forget Nu Rave, We're Into Nu Grave!: High Street Style and the Uses of Gothic Romance -- 4. Gothic Charm School, or, How Vampires Learned to Sparkle -- 5. Pretty in Black: The Goth Girl and the Whimsical Macabre -- 6. Happy Nights Are Here Again': Having a Laugh with Vampires and Other Monsters -- 7. I'm the Shoreditch Vampire': Making Over Goth Masculinities in Television Comedy -- 8. Swishing about and spookiness': Whitby and Gothic Literary Tourism from Bram Stoker's Dracula to Paul Magrs's Never the Bride.
Includes bibliographical references (pages 189-201), filmography (pages 201-203), and index.
Keywords: Gothic fiction (Literary genre) -- 21st century -- History and criticism; Gothic revival (Literature); Goth culture (Subculture)